Assessing of Operational Capabilities Impact on Process Management in Halal Food Manufacturing Companies - Norjayadi Tamam, Mohamad; Zainoren Abang, Abang; Abdurahman; Abdullah, Firdaus; Yacob, Yusman (International Journal of Psychosocial Rehabilitation, 2020)
Interest in operational capabilities and its influence on firm’s competitive advantage and performance have generated a large research stream within the operations management strategy literature particularly in automotive and electronic industry. However, little has been done on the antecedents of operational capabilities leading to process management in food industry particularly on Halal food industry. Specifically, the present study serves as a groundwork to examine the operational capabilities dimension and its effect on process management in the Halal food manufacturing industry. Operational capabilities in this study is operationalized as a higher order construct which consists of innovation, improvement, cooperation, customization, responsiveness, and reconfiguration. A quantitative approach was adopted using self-administered questionnaire. By using field data collected from 229 Halal food manufacturing industry in Sarawak, all postulated relationships are examined using partial lease squares structural equation modeling (PLS-SEM) technique. The findings suggest that operational improvement, cooperation, customization, responsiveness, and reconfiguration have significant effect on the process management. This study highlights the importance of operational capabilities dimension as a tool to strengthen the process management of the firm. This study also provides the managerial implications to the halal food manufacturing industry as an economic engine of growth and future directions of the research also been discussed.